Special Drawing Rights : The Role of Language. (Pamphlet Series, 1971)
This paper deals with one aspect of the drafting of the amendment, the choice of language, and more particularly the two expressions-special drawing rights and a supplement to existing reserve assets. It shows the contribution that language can make, if not to the reconciliation of opposing views, then at least to their accommodation. The paper highlights that the effort expended in the search for a suitable terminology was only part of the much larger effort required to reach agreement, but was considerable. The choice of terminology enabled the proponents of divergent views to insist that their opinions had prevailed.